Functional thin films as cathode/electrolyte interlayers: a strategy to enhance the performance and durability of solid oxide fuel cells. Issue 33 (15th August 2022) - Machado, Marina; Baiutti, Federico; Bernadet, Lucile; Morata, Alex; Nuñez, Marc; Ouweltjes, Jan Pieter; Fonseca, Fabio Coral; Torrell, Marc; Tarancón, Albert
Abstract : LSM/SDC functional bilayer fabricated by PLD (pulsed laser deposition) presenting a self-assembled periodic nanocomposite applied as a functional cathode layer on an SOFC resulting in an enhanced performance and durability of the tested cells. Abstract : Electrochemical devices such as solid oxide fuel cells (SOFC) may greatly benefit from the implementation of nanoengineered thin-film multifunctional layers providing, alongside enhanced electrochemical activity, improved mechanical and long-term stability. In this study, an ultrathin (400 nm) bilayer of samarium-doped ceria and a self-assembled nanocomposite made of Sm0.2 Ce0.8 O1.9 -La0.8 Sr0.2 MnO3-δ was fabricated by pulsed laser deposition and is employed as a functional oxygen electrode in an anode-supported solid oxide fuel cell. Introducing the functional bilayer in the cell's architecture results in a simple processing technique for the fabrication of high-performance fuel cells (power density 1.0 W cm −2 at 0.7 V and 750 °C). Durability tests were carried out for up to 1500 h, showing a small degradation under extreme operating conditions of 1 A cm −2, while a stable behaviour at 0.5 A cm −2 (2.8% Vin kh −1 ). Post-test analyses, including scanning and transmission electron microscopy and electrochemical impedance spectroscopy, demonstrate that the nanoengineered thin film layers remain mostly morphologically stable after the operation.